Hot Compressed Water Pretreatment Of Oil Palm Residues To Enhance Glucose Recovery - Goh, Chun Sheng (2011)
This study presents the pretreatment of oil palm residues using hot compressed water (HCW) to enhance glucose recovery in enzymatic hydrolysis for the production of second generation bio-ethanol. Oil palm residues chosen in this work is oil palm fronds (OPF) and empty fruit bunch (EFB). The experiments were carried out in a batch system using a 10 bar pressurized reactor. Response surface methodology (RSM) in conjunction with central composite design (CCD) was used to optimize the response and effect of reaction temperature, reaction time and liquidsolid ratio on the pretreatment process. Response investigated is glucose recovery for OPF and EFB respectively.